2021
DOI: 10.3390/polym13213643
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surface Functionalization of PLGA Composite to Immobilize Extracellular Vesicles

Abstract: Endothelialization by materials provides a promising approach for the rapid re-endothelialization of a cardiovascular implantation. Although previous studies have focused on improving endothelialization through the immobilization of bioactive molecules onto the surface of biodegradable implants, comparative studies of effective surface modification have not yet been reported. Here, we conducted a comparative study on the surface modification of poly(lactide-co-glycolide) (PLGA)-based composites to graft mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Materials with a higher Mw and more cations are more toxic, and even low Mw polycations might disrupt cell membranes over time, indicating that there is no such thing as “non-toxic” polycations [ 120 ]. However, it has been reported that extracellular vesicles derived from MSCs, which are released from PEI surface-modified PLGA materials, could reduce the inflammation of endothelial cells and increase angiogenesis [ 121 ].…”
Section: Plga Scaffold Surface-modified Materialsmentioning
confidence: 99%
“…Materials with a higher Mw and more cations are more toxic, and even low Mw polycations might disrupt cell membranes over time, indicating that there is no such thing as “non-toxic” polycations [ 120 ]. However, it has been reported that extracellular vesicles derived from MSCs, which are released from PEI surface-modified PLGA materials, could reduce the inflammation of endothelial cells and increase angiogenesis [ 121 ].…”
Section: Plga Scaffold Surface-modified Materialsmentioning
confidence: 99%
“…Additionally, extracellular vesicles derived from melatonin-preconditioned hUCMSC cultured in CDM (mEV) were immobilized onto the PMEZ scaffold after coating with positively charged polyethylenimine (PEI) to capture EVs and maximize therapeutic activities with sustained release of EVs in biological condition. 53 The formation of highly porous structures to enable cell migration and diffusion of bioactive components between scaffolds and peripheral tissues was monitored using cross-sectional images from scanning electron microscopy. All types of scaffolds showed similar porosity with the addition of MH-RA, ECM, and ZnO-ALA due to the use of an equal ratio of ice particles for controlling scaffold porosity (Fig.…”
Section: Comparative Analysis Of Mirna Pro Ling For Cdm Ev and Cdm Mevmentioning
confidence: 99%
“…To maximize biological activities of released mEVs from the PLGA-based scaffold, polyethylenimine (PEI) was coated onto the surfaces of scaffolds as already established protocol from our Lab. 53 Continuously, mEVs were loaded onto the hydrated PEI-coated PMEZ scaffolds. The cross sectioned morphology of the scaffolds was observed using scanning electron microscopy (SEM; GENESIS-1000, Emcraft, Gwangju, Korea).…”
Section: Fabrication and Characterizations Of Scaffoldsmentioning
confidence: 99%
“…Along the line of these thoughts, it can be concluded that PEI-EVs are not inert and play a key role in determining recipient cells' fates. [131] Woo et al [132] have conducted a study to compare the effects of different surface modification strategies on PLGA composites. Such research was few in number.…”
Section: Noncovalent Coupling On Evs Surfacementioning
confidence: 99%
“…[ 131 ] Woo et al. [ 132 ] have conducted a study to compare the effects of different surface modification strategies on PLGA composites. Such research was few in number.…”
Section: The Evs‐biomaterials System In Tissue Regenerationmentioning
confidence: 99%